Development of gas metering calibration system for domestic gas meter [microfilm] - 321383 Liaw, Kim Kiat (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Sarjana Kejuruteraan (Gas)) - Universiti Teknologi Malaysia, 2002